2022
DOI: 10.3389/fpls.2022.895402
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Rice Cropping Systems Mitigates Ecological Footprints and Enhances Grain Yield in Central China

Abstract: Intensive cereal production has brought about increasingly serious environmental threats, including global warming, environmental acidification, and water shortage. As an important grain producer in the world, the rice cultivation system in central China has undergone excessive changes in the past few decades. However, few articles focused on the environmental impacts of these shifts from the perspective of ecological footprints. In this study, a 2-year field trial was carried out in Hubei province, China, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…For example, the garlic-rice system was found to have significantly higher GWP but significantly lower GHGI than the wheat-rice system [26]. The ratoon rice cropping system (RR) showed similar direct GWP to the rice-wheat cropping system, which was 33% lower than that of the double rice cropping system (DR) [27]. These studies suggest that the different rotated crops in a given rice-based cropping system may affect the GWP and GHGI of the system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the garlic-rice system was found to have significantly higher GWP but significantly lower GHGI than the wheat-rice system [26]. The ratoon rice cropping system (RR) showed similar direct GWP to the rice-wheat cropping system, which was 33% lower than that of the double rice cropping system (DR) [27]. These studies suggest that the different rotated crops in a given rice-based cropping system may affect the GWP and GHGI of the system.…”
Section: Introductionmentioning
confidence: 99%
“…RR and DR require different management practices (such as tillage and water management) and agricultural inputs (such as seeds, fertilizers, pesticides, and labor), which may lead to differences in GHG emissions, as well as in yield performance and economic benefits [30]. Previous studies have demonstrated that RR generally has lower annual GWP, GHGI, and carbon footprint [27], and higher NEEB compared with DR [28,30]. In addition, Xu et al [25] have comprehensively studied the GHG emissions, carbon footprint, and NEEB of RR and DR, which has greatly improved our understanding of the GHG emissions and NEEB of the two cropping systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fu et al (2013) used the ecological footprint index method to predict grain security and ecological sustainable development in China in 2030 [4]. Zhou et al (2022) studied the impact of rice planting system on the environment from the perspective of ecological footprint [5]. Tian et al (2016) used stochastic frontier analysis to measure the environmental efficiency of farmers' production in China [6], and Zhang et al (2019) used stochastic frontier analysis to calculate the green total factor productivity (GTFP) of countries along the Belt and Road [7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to favorable climatic conditions, double-cropped rice is one of the main types of production in central China. Farmland is waterlogged during most of the year, leading to changes in soil structure, which in turn accelerates nutrient loss and encourages farmers to develop the habit of over-fertilizing [63,64]. For example, the 1215 kg CO 2 -eq ha −1 nitrogen fertilizer input reported by Li et al in rice production in central China is three times higher than the one in this study [36].…”
Section: Effects Of Different Water and Fertilizer Management On The ...mentioning
confidence: 51%